Role of Farm Women in Livestock Management in Rice-Livestock Farming System - Sujit K. Nath; S. Chowdhury; R.K. Raj (Journal of Agricultural Extension Management, 2025)
This paper studies the role performance of farm women in rice-livestock farming system in Balas ore district of Odis ha during 2009-2011. A sample of 240 farm women belonging to marginal and small farming category were selected purposively from 12 randomly selected villages, representing all the community development blocks of the district. The study revealed that majority of small and marginal farming households of the district were rearing goats as compared to cows and poultry birds. Farm women were performing their role better in providing feed and water to animals (92.5%) than any other activities. The lowest involvement of farm women in livestock management was in liasoning with the veterinary staff for treatment with a participation index of only 13.8%